PENGARUH PEMBERIAN KEFIR SUSU SAPI TERHADAP KADAR KOLESTEROL TOTAL TIKUS JANTAN SPRAGUE DAWLEY - Wahdania, Finta; Pramono, Adriyan (Journal of Nutrition College, 2012)
Background : A high serum cholesterol level might become one of contributing risk factor for development of cardiovascular disease (CVD). Serum cholesterol level could decreased by acid lactic bacteria (ALB) content. Kefir, one of probiotic product have been claimed as a cholesterol-lowering agent. The purpose of this research was to determine effect of cwo milk kefir to serum total cholesterol level in animal model. Method : true-experimental by using pre post test with randomized control group design. Twenty eight male Sprague dawley rat were divided into four group (K,P1, P2, P3) and induced by high cholesterol diet. Intervention started from 1,5 ml; 2 ml and 3 ml of kefir respectively to P1, P2 and P3 for fifteen days. Cholesterol level was examined by CHOD-PAP method. Data was examined by using one way ANOVA. Result : Total cholesterol level decreased significantly in all group but there is no defference between group. The highest reduction of total cholesterol was 31,45%, found in group P3 followed by 31,40% for K; 30,90% for P2 and 27,04 % for P1. Conclusion : kefir administration did not contribute in lowered total cholesterol level, result of this study did not support administration of kefir as a cholesterol-lowering agent